2018
DOI: 10.1371/journal.pone.0208171
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota signatures in cystic fibrosis: Loss of host CFTR function drives the microbiota enterophenotype

Abstract: BackgroundCystic fibrosis (CF) is a disorder affecting the respiratory, digestive, reproductive systems and sweat glands. This lethal hereditary disease has known or suspected links to the dysbiosis gut microbiota. High-throughput meta-omics-based approaches may assist in unveiling this complex network of symbiosis modifications.ObjectivesThe aim of this study was to provide a predictive and functional model of the gut microbiota enterophenotype of pediatric patients affected by CF under clinical stability.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(145 citation statements)
references
References 50 publications
4
129
1
Order By: Relevance
“…Furthermore, the intestinal inflammation in patients with cystic fibrosis might be related to alterations of the composition of the gut microbiota (de Freitas et al, 2018). It has been demonstrated that the gut microbiota pattern is caused by cystic fibrosis transmembrane conductance regulator (CFTR) function impairment (De Lisle, 2016;Vernocchi et al, 2018). The interaction of cystic fibrosis host-gut microbiota provides new insights to the treatments or interventions to enhance intestinal function and nutritional status of children suffering from cystic fibrosis.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Furthermore, the intestinal inflammation in patients with cystic fibrosis might be related to alterations of the composition of the gut microbiota (de Freitas et al, 2018). It has been demonstrated that the gut microbiota pattern is caused by cystic fibrosis transmembrane conductance regulator (CFTR) function impairment (De Lisle, 2016;Vernocchi et al, 2018). The interaction of cystic fibrosis host-gut microbiota provides new insights to the treatments or interventions to enhance intestinal function and nutritional status of children suffering from cystic fibrosis.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Fecal volatile organic compounds (VOCs) from 11 NSCLC patients were detected according to Vernocchi et al [29] by using the carboxen-polydimethylsiloxane coated fiber (CAR-PDMS) (85 μm) and the manual SPME holder (Supelco Inc., Bellefonte, PA, USA) according to Vernocchi et al [29]. The SPME fiber was exposed to each sample for 45 min.…”
Section: Gut Microbiota Metabolomics Profiling Generation Of Volatilomentioning
confidence: 99%
“…Indeed, big data are usually produced by considering an order of tens or hundreds of samples, but this point (i.e., the number of samples) can be established for each produced chemometric model using different multivariate statistical methods (e.g., Hotelling T2, number of misclassifications (NMC), area under the receiver operating characteristics curves (AUROC), and discriminant Q2; in the case of the latter, in contrast to NMC and AUROC, PLS-DA models with low complexity compared to PLS models are preferred). Therefore, each integrated model based on omics-derived data needs to be validated for each sample set under analysis [ 92 , 93 , 94 , 95 ].…”
Section: Stratification Of Complex Disease Phenotypes Early Intermentioning
confidence: 99%
“…In this way, the integrated generated model can be validated for each type of sample set (e.g., row data from GC-MS, LC-MS, 1 H-NMR, etc.) and for each patient and/or reference subject dataset (e.g., phenomics data) [ 92 , 93 , 94 , 95 ].…”
Section: Stratification Of Complex Disease Phenotypes Early Intermentioning
confidence: 99%